2021
DOI: 10.1021/jacs.0c11960
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of (2S,2′S)-Lomaiviticin A

Abstract: Lomaiviticin A (1) is a genotoxic C 2 -symmetric metabolite that arises from the formal dimerization of two bis(glycosylated) diazotetrahydrobenzo [b]fluorenes. Here we present a synthesis of the monomer 17 and its coupling to form (2S,2′S)-lomaiviticin A (4), an unnatural diastereomer of 1. (2S,2′S)-Lomaiviticin A ( 4) is significantly less genotoxic, a result we attribute to changes in the orientation of the diazofluorene and carbohydrate residues, relative to 1. These data bring the importance of the config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…These compounds show complex stereochemistry, which is crucial to their biological activities. 108 So far, the total chemical synthesis of lomaivicitins has still not been conquered. Very recently, Herzon and coworkers carried out microED studies and successfully revised the structure of lomaivicitins, and especially identified the dimerized C-C bridge is located at C5, instead of C6 (Fig.…”
Section: Chemical Synthesis Of Cremeomycin and Kinamycin And Hydrazid...mentioning
confidence: 99%
“…These compounds show complex stereochemistry, which is crucial to their biological activities. 108 So far, the total chemical synthesis of lomaivicitins has still not been conquered. Very recently, Herzon and coworkers carried out microED studies and successfully revised the structure of lomaivicitins, and especially identified the dimerized C-C bridge is located at C5, instead of C6 (Fig.…”
Section: Chemical Synthesis Of Cremeomycin and Kinamycin And Hydrazid...mentioning
confidence: 99%
“…Of note, lomaiviticin A contains two diazotetrahydrobenzo­[ b ]­fluorene (diazofluorene) residues and four deoxyglycosides, two of which are β-linked, and a single carbon–carbon bond linking each half of the molecule. Due to its potent biological activity (low nM half-maximal inhibitory potencies (IC 50 s) against cultured human cancer cell lines), unique mechanism of action (induction of DNA double-strand breaks (DSBs)), and complex structure, the total synthesis of structure 1 was pursued for over 20 years . Despite these extensive efforts, there had not been a complete synthetic route to 1 or single-crystal X-ray analysis of any natural isolate, leaving the original assignment untested.…”
Section: Introductionmentioning
confidence: 91%
“…Fluorene is a common core structure of functional materials and biologically active pharmaceuticals. ,, Recently, the Wen group has presented a palladium-catalyzed approach for synthesis of substituted fluorenes 83 via sequence Mizoroki–Heck/reductive Heck domino reactions between cyclic diaryliodoniums 81 and terminal alkenes 82 in the presence of Et 3 N/HCOONa as base/reducing agents (Scheme ). Mechanistically, palladium species coordinate with cyclic diaryliodoniums 81 , and subsequent insertion into alkenes followed by β-H elimination process generates a key intermediate int11 .…”
Section: Synthetic Applications Of Cyclic Aryliodoniumsmentioning
confidence: 99%